Cohesion and Coherence in Translation - Khader, Karawan (2004)
A Master of Arts Thesis Submitted to the Department of English & Translation Studies by Karawan Khader Titled, "Cohesion and Coherence in Translation," June 3, 2004. Advisor Dr. Said Faiq. Thesis available only in hard copy in AUS Archives.